2018
DOI: 10.3390/coatings8120471
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Optimum Concentration of Benzimidazole Improving the Cathodic Disbonding Resistance of Epoxy Coating

Abstract: This study is aimed to evaluate the effect of concentrated benzimidazole (BIM) on the cathodic disbonding (CP) of an epoxy coating applied on steel substrate. For this purpose, the polymeric coatings, formulated with different concentrations of BIM (0 wt.%, 0.5 wt.%, 0.75 wt.%, and 1 wt.%, were subjected to the CP test at the potential of −1.2 V vs. Ag/AgCl during 24 h immersion in 3.5 wt.% NaCl solutions. The optimum formulation was found through taking advantage of the CP test results, FESEM/EDX, and EIS dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Another use of BnZ and its derivatives is in supra-molecular assemblies with intriguing features for various uses, such as thermostable polymers, adsorbent materials, nano-containers, and liquid crystals for electronic conduction. For the last few years, it has been seen in a lot of research in the area of polybenzimidazole (PBI) derivatives, such as for solid electrolytes of fuel cells [ 40 , 41 , 42 , 43 , 44 ], fiber [ 45 ], thin coatings [ 46 ], advanced protective coverings [ 47 ], or to remove palladium, Th, and U from a watery medium [ 48 ]. PBI-based technologies exist in Charlotte, North Carolina, used in the pioneering industrial applications for firefighter safety in Europe, United States, and Middle East, with 32 years of expertise.…”
Section: Multifaceted Efficacy Of Benzimidazolementioning
confidence: 99%
“…Another use of BnZ and its derivatives is in supra-molecular assemblies with intriguing features for various uses, such as thermostable polymers, adsorbent materials, nano-containers, and liquid crystals for electronic conduction. For the last few years, it has been seen in a lot of research in the area of polybenzimidazole (PBI) derivatives, such as for solid electrolytes of fuel cells [ 40 , 41 , 42 , 43 , 44 ], fiber [ 45 ], thin coatings [ 46 ], advanced protective coverings [ 47 ], or to remove palladium, Th, and U from a watery medium [ 48 ]. PBI-based technologies exist in Charlotte, North Carolina, used in the pioneering industrial applications for firefighter safety in Europe, United States, and Middle East, with 32 years of expertise.…”
Section: Multifaceted Efficacy Of Benzimidazolementioning
confidence: 99%
“…Polybenzimidazole (PBI) derivatives: solid electrolyte for fuel cells [46], fibers [47], thin coatings [48], protective coatings for aerospace applications [49], or for the removal of uranium, thorium, and palladium from aqueous medium [50] are intensively studied in recent years. With an experience of 32 years, PBI Performance Products from Charlotte, North Carolina, is the leader in firefighter safety in Europe, USA, and the Middle East.…”
Section: Applications Of Benzimidazole Derivatives In Other Fields Thmentioning
confidence: 99%
“…They found that the presence of corrosion inhibitor in epoxy coating enhanced the adhesion of the coating and its resistance to cathodic disbonding. Other researches have also reported the effect of various inhibitors and additives on the improvement of cathodic disbonding resistance [18][19][20].…”
Section: Introductionmentioning
confidence: 99%